Motorcycle workshop selection recommendation system in gading serpong using the topsis method - Natapura, Septaria Dwi; Twince, Fenina Adline; Kusnadi, Adhi; Nainggolan, Rena (Jurnal Mandiri IT, 2024)
In Indonesia, motorbike repair shops have become a necessity for motorbike riders. The large number of motorcycle repair shops makes it difficult for users to determine the right repair shop according to their needs. Thus, the role of the recommendation system is needed. In order to meet the need for various criteria, a recommendation system for selecting a motorbike repair shop was built using a case study in Gading Serpong. The criteria used are distance, service, speed, price, and comfort of the waiting area. The TOPSIS method (Technique for Order Preference by Similarity to Ideal Solution) is a multi-criteria method that is computationally efficient and is able to measure the relative performance of various decision alternatives in simple mathematical form. Therefore, this research system was built using the TOPSIS method. The test results in this research show that the TOPSIS method has been implemented correctly. Apart from that, a success test of the recommendation system has been carried out by distributing questionnaires, with a success percentage of 82.24%. The questionnaire results obtained have also been tested using Cronbach Alpha, with a result of 0.81, which means that the questionnaire results obtained can be trusted